To expand the expression \( \frac{5}{6}(9b - 12) \), we distribute \( \frac{5}{6} \) to both terms inside the parentheses:
-
Distributing \( \frac{5}{6} \) to \( 9b \): \[ \frac{5}{6} \cdot 9b = \frac{45}{6}b = 7.5b \]
-
Distributing \( \frac{5}{6} \) to \( -12 \): \[ \frac{5}{6} \cdot -12 = -\frac{60}{6} = -10 \]
Combining both parts, the expanded expression is: \[ 7.5b - 10 \]
So, to fill in the blank, the complete expression is: \[ b + \text{(fill in the blank)} = 7.5b - 10 \]
Thus, the answer for the blank would be: \[ -10 \]